Cathode and anode materials for alkali metal electrochemical reactions in energy storage systems – current state of the art and potential developments - Rejmer, Wojciech; Racewicz, Szymon; Wierzbicki, Sławomir (Chemical and Process Engineering: New Frontiers, 2026)
European and world economies are displaying increased use of renewable energy sources (RES). Energy sources such as wind energy, solar energy and water current energy, while clean and not emitting carbon dioxide, do not allow for stable electrical energy production due to their dependence on weather conditions. Current development trends are focused on the production of energy storage units, which will allow for stable electricity production from renewable sources. One unit investigated by researchers is flow and steady state high-capacity batteries. Ideal storage system should be characterised by high electric stability, charge-discharge reversibility, stability and low cost. The most widely used technology is ion lithium batteries. However, sources of lithium are geographically and quantitatively limited. There is an increasing interest in the application of other active metals in energy storage systems. Most active metal salts exhibit high water solubility and are available in most parts of the world. The objective of this work was to catalogue known active metals usage in energy storage, including their current and most promising applications, with a focus on the capacity of electrochemical processes and on anode and cathode materials.